Temperature dependent analytical model for submicron GaAs-MESFET - Mohamed Djouder; Arezki Benfdila; Ahcene Lakhlef (Bulletin of Electrical Engineering and Informatics, 2021)
MESFET are used in circuitsof gigahertz frequencies as they are based on gallium arsenide (GaAs) having electron mobility six times higher than that of silicon. An analytical model simulating different device current-voltage characteristics, i.e., output conductance and output transconductance of a 0.3μm gate MESFET with temperature dependence is proposed. The model is validated by comparing the results of the proposed model and those of the numerical simulation. The parameter values are computed using an intrinsic MESFET of two-dimensional geometry. In this work, the distribution of different output loads for varied applied voltages is considered. Simulation results obtainedunder temperature variation effectsfor load distribution and applied driven voltage variation are considered. The RMS and average errors between the different models and GaAs MESFET simulations are calculated to evidence the proposed model accuracy. This was demonstrated by a good agreement between the proposed model and the simulation results, which are found in good agreement. The simulation results obtained under temperature variations were discussed and found to complement those obtained in the literature. This clarifies the relevance of the suggested model analytical.